Master of furies - Feist, Raymond E. (Feist, Raymond E. Firemane, 2022)
When his wife is murdered by ruthless raiders, Declan Smith, hellbent on revenge, joins forces with a man on the same mission, while Hava, whose gift for piracy has earned the name of "The Sea Demon," closes in on those who unleashed the murderous hordes.